Analysis of the Relationship between Curriculum Quality, Facilities and Infrastructure, and Learning Time Management on Student Satisfaction in the Learning Process in High Schools - Ratnasari, Shofia Annisa; Arifin, Arifin; Hidayat, Gustina (International Journal of Business, Law, and Education, 2025)
This study aims to examine the relationship between curriculum quality, educational facilities, and time management on student satisfaction in the learning process at High Schools. Using a quantitative approach with a stratified random sampling technique, the study involved 250 students from various High Schools. Data were collected using a structured questionnaire and analyzed through multiple linear regression with the help of SPSS software. The results showed that all three independent variables—curriculum quality, educational facilities, and time management—have a simultaneous and significant influence on student satisfaction. Among the three, curriculum quality has the most dominant effect, followed by educational facilities and time management. The coefficient of determination (R²) indicated that 37.7% of the variance in student satisfaction can be explained by the three variables. These findings highlight the importance of a relevant and flexible curriculum, adequate school facilities, and effective learning time management in improving students' learning experience.